Using simple interrupted suture anastomoses may impair translatability of experimental rodent oesophageal surgery. Issue 5 (2nd September 2020) - Tagkalos, Evangelos; Lindner, Andreas; Gruber, Gudrun; Lang, Hauke; Heimann, Axel; Grimminger, Peter P.; Muensterer, Oliver J.; Oetzmann von Sochaczewski, Christina
Abstract: Background/purpose: Irreproducibility and missing translatability are major drawbacks in experimental animal studies. Hand-sewn anastomoses in oesophageal surgery are usually continuous, whereas those in experimental oesophageal surgery are widely performed using the simple interrupted technique. It has been implicated to be inferior in tolerating anastomotic tension, which we aimed to test in rats due to their importance as an animal model in oesophageal surgery. Methods: We determined linear breaking strengths for the native oesophagus ( n = 10), the simple interrupted suture anastomosis ( n = 11), and the simple stitch ( n = 9) in 8-week old Sprague–Dawley rats. Experiments were powered to a margin of error of 10% around the results of exploratory investigations. The comparison of anastomotic resilience between native organ and simple interrupted suture anastomosis was a priori powered to 99%. Results: Native oesophagi sustained traction forces of 4.25 N (95% CI: 4.03–4.58 N), but the simple interrupted suture anastomosis had only 38.6% (Δ= −2.78 N, 95% CI: −2.46 to −3.11 N, p < .0001) of the resilience of native oesophagi. Conclusions: Oesophageal division and re-anastomosis markedly decreases resilience to traction forces compared to the native organ. This effect is even more pronounced in rats compared to other species and might impair transferability of results.